Strategy for Developing Traditional Concrete Sculptures in Yan Dede's Studio - Setia pradnyana, Putu Heri; Mudana, I Wayan; Bendi Yudha, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This study aims to analyze the process of creating symbolic concrete sculptures at Yan Dede Studio through an artistic practice approach. The research focuses on the development of conceptual ideas, material exploration, and technical realization in producing sculptures with socio-cultural meaning. The method used in this research follows four stages of artistic creation: exploration, experimentation, realization, and evaluation. Data were collected through observation of the sculpting process, documentation of artistic development, and reflective analysis of the final artwork. The results show that the sculpture represents a symbolic critique of human moral conflict through the hybrid figure of a human body combined with a pig’s head holding a rooster. The work reflects the duality of human nature between rationality and instinct. This study confirms that artistic creation in concrete sculpture can function as a medium for social reflection and cultural expression in contemporary art practice.